The role of ionotropic glutamate receptors in cancer biology - Stepulak, Andrzej; Polberg, Krzysztof; Kupisz, Krzysztof; Jarząb, Agata; Grabarska, Aneta; Jeleniewicz, Witold; Kiełbus, Michał; Stryjecka-Zimmer, Marta (Contemporary Oncology/Współczesna Onkologia, 2010)
Effective treatment of different types of cancer is limited with regard to the clinical stage of the disease and/or biological properties of the tumour. Because of the low efficacy of traditional chemotherapy, new types of targeted therapy acting selectively on specific metabolic pathways pathologically deregulated in cancer cells are still needed. In the last decade glutamate signalling has emerged as a new potential therapeutic target in cancer. This review outlines the role of glutamate as a growth factor for cancer cells, the presence and function of ionotropic glutamate receptors in cancers, and the potential impact of glutamate receptor antagonists as a new generation of cytostatics. The review also describes suggested mechanisms of their activity at the molecular level.